EXPLORING NURSES’ PERCEPTIONS REGARDING IMPLEMENTATION OF THE MEDICAL TEACHING INSTITUTIONS (MTI) ACT AT SAIDU GROUP OF TEACHING HOSPITALS, SWAT (The Research of Medical Science Review, 2025)
Background: The implementation of the Medical Teaching Institutions (MTI) Act in public sector hospitals of Khyber Pakhtunkhwa, Pakistan, marks a major shift in healthcare governance. While the Act aims to improve efficiency, autonomy, and service quality, its anticipated impact on frontline healthcare workers especially nurses remain underexplored. Understanding nurses’ perceptions is vital for inclusive and effective policy implementation. Aim: This study aimed to explore the perceptions, concerns, and expectations of nurses regarding the anticipated implementation of the MTI Act at Saidu Group of Teaching Hospitals (SGTH), Swat. Methods: A qualitative research design with a phenomenological approach was employed to explore nurses’ lived experiences. Twelve registered nurses from different departments at SGTH were selected using purposive sampling. Data were collected through semi-structured, face-to-face interviews guided by open-ended questions. Interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis. Credibility was ensured through member checking, peer debriefing, and an audit trail. Results: Six major themes emerged: limited awareness and understanding, perceived benefits (such as improved accountability), perceived challenges (especially job insecurity), workplace hierarchy concerns, low readiness for change, and nurses’ expectations for inclusion and transparency. Participants expressed uncertainty, fear of marginalization, and lack of formal orientation, yet also showed willingness to contribute positively if involved in the process. Conclusion: The successful implementation of the MTI Act requires addressing nurses’ concerns through clear communication, job security assurances, inclusive decision-making, and structured readiness-building programs. Nurses’ active involvement is essential for sustainable healthcare reform.